1935
DOI: 10.3181/00379727-32-8111p
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cobra Venom on the Fujinami Rat Sarcoma

Abstract: a simple and possibly a successful method to treat and control this serious epidemic disease. Before applying this method to clinical trial here in China, we have endeavored to study its effectiveness in experimental infections, So far, the results obtained seem to indicate that with the dose employed, a significant protection has been obtained by means of this immune horse serum. The exact dosage and the possible therapeutic use of the serum after the appearance of the fever are subjects now under study.Calme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1937
1937
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…However, after 6 successive weeks, cancer progresses between the experimental and control groups were similar [ 12 ]. Kurotchkin et al discovered that cobra venom could destroy cells of the Fujinami rat sarcoma, which seemed to require direct contact between the venom and tumor cells [ 13 ]. Ligneris et al showed that African snake venoms had no effect on the great majority of tumors in humans [ 14 ].…”
Section: Early-stage Study On Snake Venoms In Cancer Therapymentioning
confidence: 99%
“…However, after 6 successive weeks, cancer progresses between the experimental and control groups were similar [ 12 ]. Kurotchkin et al discovered that cobra venom could destroy cells of the Fujinami rat sarcoma, which seemed to require direct contact between the venom and tumor cells [ 13 ]. Ligneris et al showed that African snake venoms had no effect on the great majority of tumors in humans [ 14 ].…”
Section: Early-stage Study On Snake Venoms In Cancer Therapymentioning
confidence: 99%
“…The idea of utilizing snake venom as an important source of therapeutic agents and focusing on its anticancer properties has been extensively reviewed [ 23 , 24 , 42 ]. The investigation of snake venom’s effects on cancers can be traced back as early as the 1930s [ 43 , 44 ]. Since then, various snake venom proteins—most notably, LAAO, PLA 2 , SVMP/disintegrins, and snake venom C-type lectins (SNACLEC)—have been isolated and characterized for their activity as potential anticancer agents.…”
Section: Potential Anticancer Activity Of Malaysian Cobra Venommentioning
confidence: 99%